Chiral, Heterometallic Lanthanide–Transition Metal Complexes by Design - Øwre, Anders; Vinum, Morten; Kern, Michal; Van Slageren, Joris; Bendix, Jesper; Perfetti, Mauro (Inorganics, 2018)
Achieving control over coordination geometries in lanthanide complexes remains a challenge to the coordination chemist. This is particularly the case in the field of molecule-based magnetism, where barriers for magnetic relaxation processes as well as tunneling pathways are strongly influenced by the lanthanide coordination geometry. Addressing the challenge of design of 4f-element coordination environments, the ubiquitous Ln(hfac)3 moieties have been shown to be applicable as Lewis acids coordinating transition metal acetylacetonates facially leading to simple, chiral lanthanide–transition metal heterodinuclear complexes. The broad scope of this approach is illustrated by the synthesis of a range of such complexes LnM: LnM(hfac)3(μ2-acac-O,O,O′)3 (Ln = La, Pr, Gd; M = Cr, Fe, Ga), with approximate three-fold symmetry. The complexes have been crystallographically characterized and exhibit polymorphism for some combinations of 4f and 3d metal centers. However, an isostructural set of systems spanning several lanthanides which exhibit spontaneous resolution in the orthorhombic Sohncke space group P212121 is presented here. The electronic structure and ensuing magnetic properties have been studied by EPR spectroscopy and magnetometry. The GdFe, PrFe, and PrCr complexes exhibit ferromagnetic coupling, while GdCr exhibits antiferromagnetic coupling. GdGa exhibits slow relaxation of the magnetization in applied static fields.